2002
DOI: 10.1111/j.1559-1816.2002.tb01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Attitudinal and Demographic Similarity on Protégés' Support and Satisfaction Gained From Their Mentoring Relationships

Abstract: The purpose of this study was to examine how perceived attitudinal similarity (measured as similarity in general outlook, values, and problem‐solving approach) and demographic similarity operationalized as similarity in race and gender, affected protégés' support and satisfaction from their informal mentoring relationships. Scandura and Katerberg's (1988) 3‐factor scale of mentor functions was used to measure vocational, psychosocial, and role‐modeling support. Participants were 144 protégés from diverse backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 64 publications
5
83
0
2
Order By: Relevance
“…There also needs to be a positive "alchemy" between the members of the dyad [6,18]. This could refer to the mentee's perceived similarity with the mentor, an essential component to ensure the success of the relationship [15,19]. These elements are essential but not sufficient for the appearance of results for the mentee.…”
Section: Conceptual Framework For Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…There also needs to be a positive "alchemy" between the members of the dyad [6,18]. This could refer to the mentee's perceived similarity with the mentor, an essential component to ensure the success of the relationship [15,19]. These elements are essential but not sufficient for the appearance of results for the mentee.…”
Section: Conceptual Framework For Mentoringmentioning
confidence: 99%
“…As an indicator of relationship quality: the level of trust the mentee had toward the mentor-based on Rempel and Holmes [48]-(three items); the perceived similarity-inspired from Ensher et al [19]-(four items); and satisfaction with the mentor-Ragins and Cotton [49]-(four items). The measures are unidimensional (throughout an exploratory factorial analysis) and Cronbach's Alphas are 0.741, 0.897, and 0.937, respectively, which is considered excellent [50].…”
Section: For Menteesmentioning
confidence: 99%
“…First, only the perceptions of the students were reported in this study. Since the present study focused on students' perceptions, it is likely that self-reports are the most appropriate measure for data collection (Ensher et al, 2002). The perspective of the instructors in terms of students' problem-solving skills will be reported in another paper.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Self-report data are acceptable when the data measure individuals' perceptions (Ensher, Grant-Vallone, & Marelich, 2002).The items for problem-solving practices pertained to the following variables: analogizing (five items), modeling (five items), reasoning causally (11 items), and argumentation (four items) as outlined by Jonassen's First Principles of Learning (Jonassen, 2013). The items or measures for all these variables were adapted from (Jonassen, 2013;) anchored on a 5-point Likert scale (1 = strongly disagree to 5 = strongly agree).…”
Section: Instrumentmentioning
confidence: 99%
“…Moreover, the mentor agreeing with the protégé may prove as a source of support, or possibly an indicator of similarity of thought processes. Past research has repeatedly found that similarity is related to perceptions of mentoring relationship effectiveness (Ensher, Grant-Vallone, & Marelich, 2002;Sosik & Godshalk, 2005) -assent may be an indicator of, or even an antecedent to, perceptions of similarity. Given the effect sizes obtained in this study, this agreement may be the most important communication process of all.…”
Section: Perceived Mentoring Relationship Effectiveness and Communicamentioning
confidence: 99%